Towards a Service-Based Internet 4th European Conference, ServiceWave 2011, Poznan, Poland, October 26-28, 2011, Proceedings - Abramowicz, Witold; Llorente, Ignacio M.; Surridge, Mike.; Zisman, Andrea; Vayssière, Julien; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
This volume constitutes the refereed proceedings of the Fourth European Conference, ServiceWave 2011, held in Poznan, Poland, in October 2011. The 25 revised full papers presented together with 3 invited presentations were carefully reviewed and selected from numerous submissions. They are organized in topical sections on cloud computing, security, privacy and trust, service engineering fundamentals, business services, and FI-PPP. In addition to the scientific track, 14 extended abstracts of demonstrations covering a wide spectrum of technology and application domains were accepted.
Keywords: Computer communication systems; Software engineering; Application software; Algorithms; Information storage and retrieval; Computer programming; Computer Communication Networks; Software Engineering; Information Systems Applications (incl. Internet).; Algorithm Analysis and Problem Complexity; Information Storage and Retrieval; Programming Techniques